Pengelolaan Pelatihan Pembuatan Pupuk Organik Bagi Remaja Putus Sekolah di Pampung Plumbon Karanganyar - Shintara, Galuh Ajeng (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study is to describe the planning and implementation of training dropout, describes the factors driving and the problems encountered in the training dropout organic fertilizer, and describe the impact of the activity of teenagers dropping out of school in the training of organic fertilizer in the hamlet Pampung. The approach used in this study is qualitative descriptive. Data collection was conducted using interview, observation and documentation. From the results, the data include: (1). Chemical fertilizer or inorganic fertilizer was shown to lower the quality / damage to the soil; (2). Limousine cow manure waste not managed optimally in Hamlet Pampung; (3). Dropout yet have the ability and knowledge of how to treat the sewage Limousine cow waste into something more useful; and (4). Dropout and farmers are very enthusiastic about the training activities making organic fertilizer from cow dung material Limousine. In order for this training management objectives can be achieved by optimum, then several things that must be considered are: (1). Make this activity as an activity that has a follow-up plan to the marketing process organic fertilizer; (2). Structuring membership consists primarily Pampung hamlet residents, it is to facilitate the coordination of activities in the future; (3). The need for cooperation in the management of organic fertilizers to be marketed properly and smoothly, so it can become a useful citizen entrepreneurs.